ENHANCING BREASTFEEDING MOTIVATION: THE ROLE OF HUSBANDS’ KNOWLEDGE AND SUPPORT AMONG POSTPARTUM MOTHERS - Astutik, Reni Yuli; Nining Istighosah; Stevani Basuki Putri; Fitria Rahayu (Universitas STRADA Indonesia, 2025)
Breastfeeding is a natural process that strengthens the mother–infant bond and requires patience, knowledge, and family support, especially from husbands. This study aimed to examine the relationship between maternal knowledge and husband’s support with the motivation of postpartum mothers in breastfeeding. An analytic design with a cross-sectional approach was used, involving 40 postpartum mothers selected through purposive sampling. Independent variables were maternal knowledge and husband’s support; the dependent variable was breastfeeding motivation. Data collected using questionnaires and analyzed with the chi-square test. The results were that 50% of respondents had good knowledge, 57.5% received husband’s support, and 65% had positive breastfeeding motivation. Chi-Square analysis revealed a significant relationship between maternal knowledge and husband’s support and breastfeeding motivation (p = 0.000 < 0.05). Maternal knowledge and husband’s support are critical determinants of breastfeeding motivation. Strengthening health education and encouraging active husband involvement are recommended strategies to enhance exclusive breastfeeding practices.